Bibliometric analysis of research developments on differentiated instruction - Utami, Asih; Mustadi, Ali; Sujarwo; Hidayat, Riyan; Fauziyah, Puji Yanti; Rofiki, Imam (Eurasian Society of Educational Research, 2024)
This research attempts to map the trend of research related to differentiated instruction (DI). The research was conducted in May 2023 by researching research articles in the Scopus database. The search data from Scopus used title, abstract, and keyword searches. Research articles were analyzed descriptively based on year of publication, journal name, affiliation, country, and researcher name. The article database from Scopus was analyzed through VOSviewer and RStudio software so that a bibliometric map could be depicted in research related to DI. Based on the Scopus analysis results, it showed that publications of articles related to DI had increased from 2011 to 2021, although it decreased in 2016. The journal with the largest contributor to the publication of research articles related to DI was the Teaching and Teacher Education Journal. Vrije Universitiet Brusel was the university with the most published articles on DI. The country that contributed the most to the research articles related to DI was the United States. Struyven was the most productive scholar related to DI. Through network visualization, it was revealed that the evolution map of research related to DI was divided into five clusters. © 2024 The Author(s).